2020
DOI: 10.5851/kosfa.2020.e25
|View full text |Cite
|
Sign up to set email alerts
|

Functional Chemical Components in Protaetia brevitarsis Larvae: Impact of Supplementary Feeds

Abstract: The goal of this study was to evaluate the influence of various supplementary feeds on the chemical composition and production of bioactive substances in Protaetia brevitarsis larvae. The primary feed-oak-fermented sawdust-was supplemented with a variety of substances, including aloe, apple, banana, sweet persimmon (S. persimmon) and sweet pumpkin (S. pumpkin). Crude protein and fat content were the highest in the control and S. pumpkin group, respectively. Supplementary feeds increased the content of unsatura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 19 publications
4
16
1
Order By: Relevance
“…The obtained data for total amino acids in this study were considerably similar to the previous observation on P. brevitarsis larvae (mostly third instar), which was reported by Chung et al (2013) , Noh et al (2015) , and Yoon et al (2020) . In particular, Chung et al (2013) suggested that P. brevitarsis larvae could be a potentially useful source of essential amino acids (methionine, threonine, valine, isoleucine, leucine, phenylalanine, histidine, and lysine) to humans.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The obtained data for total amino acids in this study were considerably similar to the previous observation on P. brevitarsis larvae (mostly third instar), which was reported by Chung et al (2013) , Noh et al (2015) , and Yoon et al (2020) . In particular, Chung et al (2013) suggested that P. brevitarsis larvae could be a potentially useful source of essential amino acids (methionine, threonine, valine, isoleucine, leucine, phenylalanine, histidine, and lysine) to humans.…”
Section: Resultssupporting
confidence: 91%
“…In addition, Noh et al (2015) reported that the supplementation of rice bran during fasting could slightly increase the total amino acid content of P. brevitarsis larvae. Recently, Yoon et al (2020) evaluated the supplementary effects of the five natural feeding sources, such as aloe, apple, banana, sweet persimmon, and sweet pumpkin, on the nutritional composition of P. brevitarsis larvae, and found that different feeding sources could change the proportion of essential amino acids, but did not affect the total amino acid content. Consequently, it is expected that the enrichment of some essential amino acids could be possible through dietary feeding control, but which might have little to no impact on the total amino acid content of P. brevitarsis larvae.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Protaetia brevitarsis seulensis (white-spotted flower chafer)-derived protein hydrolysates have been used as medicinal material in many Asian countries for their antioxidative, anticancer, antiobesity, antidiabetic, and hepatoprotective effects [ 7 , 8 , 9 , 10 ]. Controlled feeding patterns have also modulated the bioactive substance’s synthesis in P. brevitarsis larvae for its potential exploitation [ 11 ]. The development of health-promoting functional materials from P. brevitarsis extracts have also been investigated [ 12 ].…”
Section: Introductionmentioning
confidence: 99%